PERLINDUNGAN HUKUM KONSUMEN TERHADAP PEREDARAN PRODUK VAKSIN PALSU - Tri Astuti; Efridani Lubis; Mohammad Zakky As (Jurnal Hukum Jurisdictie, 2019)
In the Law 1945 the Unitary State of the Republic of Indonesia article 1 paragraph (3) affirmed that the State of Indonesia is a state of law. In addition, in the General Explanation of the 1945 Constitution on The System of State Government, it is explained that: Indonesia is a country based on law (Rechstaat) is not based on mere power (Machstaat). Laws are formulated to regulate and protect the interests of the community and to protect human rights. The need for law to provide Indonesian Consumer Protection is inevitable, in line with one of our national development goals, namely protecting the Indonesian nation and all Indonesian blood (the opening of the 1945 Constitution paragraph IV). In this study, the author focused on the formulation of the problem "How is the legal protection of consumers against the circulation of counterfeit vaccine products?". This research aims to find out the legal protection of consumers against the circulation of counterfeit vaccine products. While this research method is Normative Juridical. Referring to the formulation of the issue regarding the protection of consumer law against the circulation of counterfeit vaccine products, the Author concluded that the regulation of the circulation of vaccine products according to the consumer protection law is Consumer Protection regulated in Law No. 8 of 1999 the understanding of consumer legal protection is all legal certainty to provide protection to consumers.Supervision of the Food and Drug Administration (BPOM) in the circulation of vaccines is one of the biological products categorized as high risk products, so it requires special consideration and attention and stricter supervision than drug products in general. Legal settlement efforts on fake vaccines are carried out in two ways, namely through the general judiciary and outside the court.